Letters to Florence O'Donoghue regarding pension applications of various members of the Cork and Kerry Brigades with drafts of certificates and statements provided by O'Donoghue as evidence for them - O'Donoghue, Florence, 1895-1967 (1936)
Claims relate to Paddy Varien, Charles Wall, Nora Wallace, Áine Walsh, Jeremiah Walsh, John Walsh and four unidentified claimants.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Irish Republican Army; Military Service (1916-1923) Pension Board; Ireland -- History -- War of Independence, 1919-1921; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-